Long-term effects of institutional quality on financial inclusion in Asia–Pacific countries - Duc Hong Vo (Financial Innovation)
Abstract Financial inclusion has recently emerged as an important pillar for sustainable economic growth, poverty eradication, and social transformation globally. While the effects of institutional quality on financial inclusion have been widely investigated, their long-term effects have largely been underexplored, particularly for the Asia–Pacific region. We are especially interested in these long-term effects because institutional reforms require time for implementation and their impacts on various socioeconomic issues are only gradually observed. This paper has developed a new index of institutional quality for countries in the Asia–Pacific region from 2004 to 2020 using the principal component analysis. We estimate the long-term effects of institutional quality on financial inclusion using long-term estimators, including the augmented mean group and the common correlated effects mean group estimators. In our study, institutional quality is proxied by the new index developed in this paper and then by each of the five fundamental aspects of institutional quality: (i) business freedom, (ii) regulatory quality, (iii) investment freedom, (iv) government effectiveness, and (v) the rule of law. We find that improved institutional quality is fundamental to achieving financial inclusion in the region. These effects are particularly prominent in high-income countries in the Asia–Pacific region. However, a closer look at these long-term effects reveals that this effect is conditional on the income level. Interestingly, this long-term effect can be established for high-income countries such as Australia and Japan but not for Singapore. In addition, in the case of middle-income countries, the long-term effect can be confirmed for countries such as Malaysia, Indonesia, and the Philippines but not for Thailand and Vietnam. Our results show that institutional reform, albeit very important, should not be considered the only fundamental pillar ensuring financial inclusion, sustainable economic growth, and social transformation in the long run.